A supervised fuzzy measure learning algorithm for combining classifiers - Uriz, Mikel; Paternain, Daniel; Bustince, Humberto; Galar, Mikel (Information sciences, 2023)
•A new supervised fuzzy measure learning algorithm is proposed for combining classifiers.•Different from previous works, any cost function can be optimized, including those well-suited for classification problems.•Three new update policies are proposed for dealing with monotonicity constrains.•The benefit of using appropriate cost functions for classification is experimentally demonstrated.•The new proposal outperforms existing methods in both binary and multi-class problems. Fuzzy measure-based aggregations allow taking interactions among coalitions of the input sources into account. Their main drawback when applying them in real-world problems, such as combining classifier ensembles, is how to define the fuzzy measure that governs the aggregation and specifies the interactions. However, their usage for combining classifiers has shown its advantage. The learning of the fuzzy measure can be done either in a supervised or unsupervised manner. This paper focuses on supervised approaches. Existing supervised approaches are designed to minimize the mean squared error cost function, even for classification problems. We propose a new fuzzy measure learning algorithm for combining classifiers that can optimize any cost function. To do so, advancements from deep learning frameworks are considered such as automatic gradient computation. Therefore, a gradient-based method is presented together with three new update policies that are required to preserve the monotonicity constraints of the fuzzy measures. The usefulness of the proposal and the optimization of cross-entropy cost are shown in an extensive experimental study with 58 datasets corresponding to both binary and multi-class classification problems. In this framework, the proposed method is compared with other state-of-the-art methods for fuzzy measure learning.